PENGARUH BOARD OF COMMISSIONERS, GREENHOUSE GAS EMISSION DISCLOSURE DAN SUSTAINABILITY REPORT DISCLOSURE TERHADAP NILAI PERUSAHAAN DENGAN ENVIRONMENTAL PERFORMANCE SEBAGAI VARIABEL MODERASI - Meilia Eka Pratiwi; Etty Murwaningsari (EBID: Ekonomi Bisnis Digital, 2023)
In this study, the authors were interested in researching how Board of Commissioners, Greenhouse Gas Emission Disclosure and Sustainability Report Disclosure to Corporate Value with Environmental Management as Moderation Variables. This study used a population of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020 which amounted to 190 companies, according to the criteria required in this study there were only 25 manufacturing companies that were sampled for the years 2016 to 2020. This study uses multiple regression analysis with the results of research that Board of Commissioners has a positive effect on corporate value, Greenhouse Gas Emission Disclosure has no effect on corporate value and Sustainability Report Disclosure has a significant positive effect on corporate value. Environmental Management moderation variables do not strengthen the relationship of Board of Commissioners, Greenhouse Gas Emission Disclosure and Sustainability Report Disclosure to Corporate Value.